EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN MATEMATIKA REALISTIK (PMR) DITINJAU DARI KECERDASAN INTERPERSONAL SISWA SMP SE-KABUPATEN GROBOGAN TAHUN PELAJARAN 2012/2013 - Nurrofiq, Achmad; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aim of the research was to determine the effect of learning models on learning achievement viewed from studentsâ interpersonal intelligence. The learning models compared were cooperative learning model Numbered Heads Together (NHT) with Realistic Mathematics Approach (RMA) approach, Think Pair Share (TPS) with Realistic Mathematics Approach (RMA) and direct learning. This research was a quasi-experimental research using factorial design of 3x3. The population of the research was all students of the Junior High Schools in Grobogan regency. The samples of the research were seven grade students of SMP Negeri 2 Purwodadi, SMP Negeri 2 Grobogan and SMP Negeri 7 Purwodadi in Grobogan regency (88 students for for first experimental class, 96 students for second experimental class, and 92 students for control class). The samples were chosen by using stratified cluster random sampling. In collecting the data, the instruments used were multiple-choice test of learning achievement in mathematics and student interpersonal intelligence questionnaire. The technique of analyzing the data was unbalanced two-ways Anova. The results of the research are as follows: (1) the cooperative learning model NHT with RMA give better achievement in mathematics than cooperative learning model TPS with RMA, and both result in a better learning achievement in mathematics than the direct learning model; (2) there are no any differences in the learning achievement in mathematics of the students with high, medium or low interpersonal intelligence; (3) in each interpersonal intelligence, the cooperative learning model NHT with RMA give better achievement in mathematics than cooperative learning model TPS with RMA, and both result in a better learning achievement in Mathematics than the direct learning model; (4) in each learning model, the students with high, medium and low interpersonal intelligence have the same learning achievement in mathematics.Keywords:Â Â Â Â Â Â Â Â Â  NHT, TPS, RMA, interpersonal intelligence, learning achievement in mathematics